(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: E-cigarette use has become widespread globally, with 8.1 million American young adults aged 18-24 using them. This habit is linked to cancer risk, particularly for head, neck, lung, and bladder cancers, as e-cigarettes contain toxic substances like benzene and carbon monoxide. The inventor of the e-cigarette is Hon Lik from China in 2003. This study aimed to assess medical students’ awareness of e-cigarettes and their relationship to cancer in the Kingdom of Saudi Arabia. Methodology: The cross-sectional study was done in Saudi Arabia during 2023-2024. Those who had cancer prior to using e-cigarettes will be excluded, and medical students will be the inclusion criterion. For this study, 493 participants were the estimated sample size. Additionally, SPSS will perform the statistical analysis. Results: The total sample size were 493 participants. As regard knowledge and awareness score about e-cigarette smoking and cancer risk among our study participants, there were a significant portion of the participants, specifically 53.5%, possess a moderate level of knowledge regarding e-cigarette smoking. Additionally, 23.7% demonstrated a high level of awareness in this area, while 22.7% exhibited a low level of knowledge. Regarding the relation between awareness level towards e-cigarette smoking and cancer and sociodemographic characteristics, there were a statistically significant relation to the academic level of participants (p value=0.003) and the university (p value=0.001). It also showed statistically insignificant relation to gender, age, and marital status. Conclusion: The study showed that a significant proportion of participants had a moderate level of knowledge about e-cigarette smoking, with some demonstrating high awareness while others showed low knowledge levels. The study also found a statistically significant relationship between awareness levels and participants' academic level and university. These findings align with previous research indicating varying levels of awareness among medical students regarding the potential health risks associated with e-cigarette use.